A Kafālah Issues: Concept and It’s Application in Indonesian Islamic Banks - Ahmad Maulidizen; Abdul Haris Muchtar (State of Islamic Institute Langsa, 2020)
This article is to analyze the concept of kafālah and its implementation in Indonesian Islamic banking. Kafālah is a contract that is closely related to the guarantee in Islamic banking. The purpose of kafālah is to provide assistance and convenience in working on a business or project for customers. With a bank guarantee, customers can run a project or business. In order for a bank to issue a bank guarantee, the customer must have a certain amount of savings in the bank. Savings can be in the form of time deposits or demand deposits. This article is to deeply examine the concept of kafālah according to fiqh mu’amalah and its implementation in Indonesian Islamic banking with a bank guarantee product. This study is a library study with descriptive approaches, which describes and explains the analysis of kafālah contracts according to fiqh muamalah and Its application in Indonesian Islamic banks. The method of collecting data in this study is based on documentation, journals and books. Further it analyses the data using content analysis, through analyzing the library data with a scientific analysis approach. Data analysis methods are deductive, inductive and comparative. The result of the study is that Kafālah is a contract of guaranteeing (makfūl alayh) given by one party to another in which the guarantor (kāfil) is responsible for the repayment of a debt which is the right of the guarantor (makfūl). In this principle, the bank acts as a kāfil (guarantor), while the customer is the makfūl (the guaranteed party). Meanwhile in practice, the application of kafālah in Indonesian Islamic banking is employed by a certificate of bank guarantee to guarantee its customers. Bank guarantee certificate is a payment guarantee that is given by the bank to the recipient of the guarantee, either individuals or companies.